Sugar Phosphorylation Controls Carbon Source Utilization and Virulence of Candida albicans - Wijnants, Stefanie; Riedelberger, Michael; Penninger, Philipp; Kuchler, Karl; Van Dijck, Patrick (Frontiers in Microbiology, 2020)
Candida albicans is an opportunistic human fungal pathogen that relies upon different virulence traits, including morphogenesis, invasion, biofilm formation, nutrient acquisition from host sources as well as metabolic adaptations during host invasion. In this study, we show how sugar kinases at the start of glycolysis modulate virulence of C. albicans. Sequence comparison with S. cerevisiae identified four enzymes (Hxk1, Hxk2, Glk1 and Glk4) in C. albicans with putative roles in sugar phosphorylation. Hxk2, Glk1 and Glk4 demonstrate a critical role in glucose metabolism, while Hxk2 is the only kinase important for fructose metabolism. Additionally, we show that Hxk1 controls HXK2, GLK1 and GLK4 expression in the presence of fermentable as well as non-fermentable carbon sources, thereby indirectly controlling glycolysis. Moreover, these sugar kinases are important during virulence. Disabling the glycolytic pathway reduces adhesion capacity, while deletion of HXK1 decreases biofilm formation. Finally, we demonstrate that hxk2Δ/Δ glk1Δ/Δ glk4Δ/Δ and hxk1Δ/Δ hxk2Δ/Δ glk1Δ/Δ glk4Δ/Δ have attenuated virulence upon systemic infections in mice. These results indicate a regulatory role for Hxk1 during sugar phosphorylation. Furthermore, these kinases are essential during growth on glucose or fructose, and C. albicans relies on a functional glycolytic pathway for maximal virulence.